Peculiarities of Motor Fitness Dynamics of 5th-6th Grade Students During a School Year - Tkachenko, Mykyta (Physical Education Theory and Methodology, 2020)
The study purpose was to determine the impact of physical education classes on the dynamics of motor fitness of 5th-6th grade students. Materials and methods. The study participants were 17 5th grade boys and 17 6th grade boys. The study used the following methods: analysis of scientific and methodological literature, pedagogical testing and methods of mathematical statistics for processing the study results. Thematic planning of educational work was carried out based on the updated physical education curriculum for 5th-9th grades of general educational institutions. Results. There are statistically significant changes in the 5th grade boys’ results of educational standards: Test 2 “Shuttle run 4×9 m (sec)” and Test 4 “Standing long jump (cm)” (p < 0.05). The results in Test 2 improve by 6.2 %, in Test 4 by 7.1 %. There are statistically significant changes in the 6th grade boys’ results of educational standards: Test 2 “Shuttle run 4×9 m (sec)” (p < 0.1) and Test 4 “Standing long jump (cm)” (p < 0.05). The results in Test 2 improve by 4.4 %, in Test 4 by 12.9 %. Conclusions. Discriminant analysis revealed that by the multivariate mean the boys’ motor fitness at the beginning and end of the school year is classified as two different states. This indicates a positive impact of physical education classes on the dynamics of motor fitness of 5th and 6th grade boys. The level of schoolchildren’s motor fitness depends on coordination and speed-strength training carried out during physical education classes.